Optimalisasi Layanan Administrasi Melalui Pelayanan Terpadu Satu Pintu (PTSP) di MIN 2 Palembang - Yanti, Devi Rahma; Annur, Saipul; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the optimization of administrative services through the One-Stop Integrated Service (PTSP) at MIN 2 Palembang by examining input, process, output, and outcome indicators, as well as the principles of accountability and transparency, while also identifying the supporting and inhibiting factors in its implementation. The study employed a qualitative approach with data collection techniques including interviews, observations, and documentation involving parties engaged in administrative services. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results show that the optimization of administrative services through PTSP at MIN 2 Palembang has been implemented effectively. From the input aspect, the availability of human resources, facilities and infrastructure, and standard operating procedures (SOP) are considered adequate to support service implementation. In terms of process, services are carried out in an orderly and efficient manner, supported by the professionalism and discipline of the staff. The service output is reflected in the timely completion of documents, completeness of files, and minimal administrative errors. The service outcome is indicated by improved service quality and user satisfaction. The principles of accountability and transparency are implemented through clear task distribution, information openness, and the availability of a complaint mechanism.